Obesity and cardiovascular risk: a call for action from the European Society of Hypertension Working Group of Obesity, Diabetes and the High-risk Patient and European Association for the Study of Obesity. Issue 7 (July 2018) - Kotsis, Vasilios; Tsioufis, Konstantinos; Antza, Christina; Seravalle, Gino; Coca, Antonio; Sierra, Cristina; Lurbe, Empar; Stabouli, Stella; Jelakovic, Bojan; Redon, Josep; Redon, Pau; Nilsson, Peter M.; et al.
Abstract : N/A: Obesity predisposes for atrial fibrillation, heart failure, sudden cardiac death, renal disease and ischemic stroke, which are the main causes of cardiovascular hospitalization and mortality. As obesity and the cardiovascular effects on the vessels and the heart start early in life, even from childhood, it is important for health policies to prevent obesity very early before the disease manifestation emerge. Key roles in the prevention are strategies to increase physical exercise, reduce body weight and to prevent or treat hypertension, lipids disorders and diabetes earlier and efficiently to prevent cardiovascular complications.